2020
DOI: 10.1038/s41545-020-0056-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel methods for global water safety monitoring: comparative analysis of low-cost, field-ready E. coli assays

Abstract: Current microbiological water safety testing methods are not feasible in many settings because of laboratory, cost, and other constraints, particularly in low-income countries where water quality monitoring is most needed to protect public health. We evaluated two promising E. coli methods that may have potential in at-scale global water quality monitoring: a modified membrane filtration test followed by incubation on pre-prepared plates with dehydrated culture medium (CompactDry TM), and 10 and 100 ml presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…2012 ). In the MICS, an adapted membrane filtration process has been used, yielding reliable quantitative results ( Brown et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2012 ). In the MICS, an adapted membrane filtration process has been used, yielding reliable quantitative results ( Brown et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The compounding complexity required for reliable results suggests that qPCR in its current form may be unsuitable for routine monitoring purposes except in particularly well-resourced laboratories that regularly process sufficient sample numbers to warrant the equipment, properly maintain assay materials, and ensure sustained institutional experience. By contrast, culture-based FIB detection has grown increasingly accessible following recent efforts to develop low-cost field tests that can be performed with minimal equipment at ambient temperatures [ 125 , 169 , 170 ]. While still requiring substantial resources and expertise, dPCR requires fewer controls and precise reference materials than qPCR because it is robust to matrix interference and offers absolute quantification, features which may position dPCR to be increasingly adopted for general use [ 171 ].…”
Section: Molecular Methods: Challenges and Advancesmentioning
confidence: 99%
“…There are several water quality tests that could potentially be integrated in household surveys (Bain et al 2012). In the approach used in MICS an adapted membrane filtration process has been used, yielding reliable quantitative results (Brown et al 2020). The costs are approximately $2.5 per test using the new "E. coli only” Compact Dry plates and $1500 per team for hardware (mainly the filtration equipment) but these are expected to reduce over time.…”
Section: Discussionmentioning
confidence: 99%
“…northern Nigeria, Afghanistan). Ambient temperature and phase change incubators are both potential solutions (Brown et al 2011) and CompactDry™ plates have been shown to perform favourably when compared to reference methods when incubated at ambient temperature in Bangalore, India (Brown et al 2020).…”
Section: Discussionmentioning
confidence: 99%